PENGARUH USIA DAN LATAR BELAKANG PENDIDIKAN TERHADAP KINERJA GURU PONPES KARANGASEM - Ikfi, Sururi; Abidin, Munirul; Zuhroh, Ni'matuz (Universitas Islam Negeri Alauddin Makassar, 2024)
The success of an educational institution in improving its quality is heavily influenced by the performance of its teachers as one of the key factors. Various aspects affect teacher performance, including age and educational background. Based on several studies, these two factors play a significant role in determining the level of teacher performance. The purpose of this study is to examine the extent to which teachers' age and educational background influence their performance in an educational foundation in Lamongan Regency. This study employs a quantitative approach, with data collected through questionnaires distributed to 102 teachers in three educational institutions under the foundation. The questionnaires were designed to measure three main variables: teacher age, educational background, and teacher performance. The data collected were analyzed using multiple linear regression to determine the extent to which teacher age and educational background impact their performance. The data processing was conducted using SPSS 27 software. The findings reveal that teacher age (X1) and educational background (X2) have a positive and significant influence on teacher performance (Y), as evidenced by the significant values of X1 and X2, which were both <.001. The t-value for X1 was 5.042, while for X2, it was 4.454. Additionally, the combined variables of teacher age and educational background simultaneously influenced teacher performance, with a significance level of p= 0.001 and an impact percentage of 5.4%. Thus, it can be concluded that both factors significantly influence teacher performance within the foundation.